2011
DOI: 10.1021/ie1010977
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Polymer Solutions from Macroscopic Properties: Application to the Perturbed Chain Statistical Associating Fluid Theory Equation of State

Abstract: In this work, a parametrization strategy that allows the estimation of polymer molecular parameters from a predefined set of macroscopic properties is presented. The parametrization scheme has been developed in terms of the polymer−solvent interaction parameter (χ) and the Hildebrand parameter, which are readily available in the literature for a large variety of solvents and polymers. In this way neither extensive experimental data nor complex optimization schemes are necessary. The proposed parametrization st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The PC-SAFT EOS model developed by Gross et al shows excellent performance in predicting the physical and thermodynamic properties of vapor, liquid, and supercritical fluids in polymer systems. ,,,, Its applicability covers fluid systems from small to large molecules, including normal fluids, water, alcohols, ketones, polymers, copolymers and their mixtures. Castro-Marcano et al investigated the accuracy of the PC-SAFT EOS in various polymer solution systems, and the phase equilibria calculation results indicated that the binary and ternary polymer solutions were in agreement with experimental data in most cases. Krallis et al employed the PC-SAFT EOS to calculate the physical and thermodynamic properties in vapor and liquid phase of the catalytic olefin (co)­polymerization industrial applications.…”
Section: Steady-state Modelingmentioning
confidence: 93%
“…The PC-SAFT EOS model developed by Gross et al shows excellent performance in predicting the physical and thermodynamic properties of vapor, liquid, and supercritical fluids in polymer systems. ,,,, Its applicability covers fluid systems from small to large molecules, including normal fluids, water, alcohols, ketones, polymers, copolymers and their mixtures. Castro-Marcano et al investigated the accuracy of the PC-SAFT EOS in various polymer solution systems, and the phase equilibria calculation results indicated that the binary and ternary polymer solutions were in agreement with experimental data in most cases. Krallis et al employed the PC-SAFT EOS to calculate the physical and thermodynamic properties in vapor and liquid phase of the catalytic olefin (co)­polymerization industrial applications.…”
Section: Steady-state Modelingmentioning
confidence: 93%
“…The pure-component parameters for pyridine, NMP, and CS 2 were determined by simultaneous fitting to experimental vapor pressure and liquid density data, while parameters for methanol were taken from the literature . Coal was modeled as a polydisperse polymer; therefore, its molecular parameters were obtained by regressing experimental binary mixture data as proposed by Gross and Sadowski. , Recently, an alternative approach based on Flory–Huggins and Hildebrand solubility parameters has been proposed for estimation of PC-SAFT polymer parameters . The molecular parameters of the PC-SAFT model for the coal samples and solvents investigated in this study are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Phase transitions in various model systems [1][2][3][4][5] are of interest to materials science to understand various phenomena 6 and emergence of new properties in materials. [7][8][9][10] Hence the choice of a model system is important to exploit such emergence of novel properties in materials.…”
Section: Introductionmentioning
confidence: 99%